Efficacy of Medical Adherence on Quality of Life Among Cardiac Patients - Chavhan , Ashutosh Vijay; Verma, Ranjana; Verma , Mamta; Dixit, Priyanshi (National Journal of Community Medicine, 2024)
Background: Nonadherence is linked to poor outcomes and impaired QOL. The objective is to find out the efficacy of medical adherence on quality of life among CAD Patients. Methodology: A descriptive cross-sectional study was conducted among 130 cardiac patients, who were coming in OPD of various urban centres of Bhopal. Data collection was done from September to October 2022 using a purposive sampling framework. Medical adherence and quality of life were assessed using self-administered MAS-CAD and WHOQOL-BREF respectively. Statistical analysis: Chi-squared test, Fisher's exact test, Kruskal Wallis and Mann Whitney test were used. The correlation between medication adherence and quality of life was analysed using the Spearman rank correlation coefficient. Results: The majority of the participants reported high (58.0%) medical adherence and were significantly correlated with variables like gender, occupational status, level of physical activity, and surgical history. Qol (<0.001), and its domains (physical, psychological and environmental) were also significantly correlated with medical adherence. Conclusion: Better Medical adherence was associated with a high quality of life among CAD patients. Males and Homemakers or unemployed had better medical adherence. A better understanding of the factors affecting medical adherence and quality of life is necessary.